Training and Provision of Information Related to The Accessibility of Official Higher Education Institutions for High School Students of The Same Level in Pekalongan City - Arditya Prayogi; Ulfa Kurniasih; Ahmad Faridh Ricky Fahmy (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
Education plays a vital role in human life, serving as a means to achieve a high quality of life. Within the realm of formal education, higher education holds particular significance in enhancing the human resources of a nation and contributing to their continual improvement. The objective of this service initiative is to provide comprehensive information on the official college selection process and deliver training through entrance examination questionnaires, enabling participants to better equip themselves for the official college entrance examinations. This community service endeavor primarily utilizes socialization and facilitates access to official school information, achieved through collaboration with external service partners. Specifically, the